A robust plasma-based laser amplifier via stimulated Brillouin scattering. (11th October 2021) - Alves, E P; Trines, R M G M; Humphrey, K A; Bingham, R; Cairns, R A; Fiúza, F; Fonseca, R A; Silva, L O
Abstract: Brillouin amplification in plasma is more resilient to fluctuations in the laser and plasma parameters than Raman amplification, making it an attractive alternative to Raman amplification. In this work, we focus on high plasma densities, n 0 > n c r / 4, where stimulated Raman scattering is not possible and laser beam filamentation is the dominant competing process. Through analytic theory and multi-dimensional particle-in-cell simulations, we identify a parameter regime for which Brillouin amplification can be efficient while maintaining filamentation of the probe at a controlled level. We demonstrate pump-to-probe compression ratios of up to 72 and peak amplified probe fluences over 1 kJ cm −2 with ≃ 50 % efficiency. High pulse quality is maintained through control of parasitic filamentation, enabling operation at large beam diameters. Provided the pump and probe pulse diameters can be increased to 1 mm, our results suggest that Brillouin amplification can be used to produce sub-picosecond pulses of petawatt power.